Desenvolvimento inicial de variedades e clones de cana-de- açúcar em Latossolo Vermelho Distrófico, Aparecida do Taboado-MS - Abranches, Jorge L.; Bolonhezi, Antônio César [UNESP] (Revista Brasileira de Ciencias Agrarias, 2011)
In Brazil, as in other sugar cane (Saccharum spp.) producing countries, varieties and clones have been continuously developed and tested in order to obtain varieties better adapted to changes in climate, soils and management, seeking a better performance in soils and climates of low agricultural suitability for the culture. In this study, the initial vegetative growth and performance of five sugar cane clones (CT96-3095, CT95-3079, CT95-1425, CT96-3024, CT92-1882) and two varieties (SP81-3250 and SP91-1049) were evaluated in an environment characterized by soils of low fertility and sandy texture. The experiment was carried out in a randomized design with seven treatments, consisting of the two sugar cane varieties and five clones. The plots contained six 15 meters sugar cane rows with a line spacing of 1.50 m. The average tiller number, tiller leaf area, vegetative cover, shoot biomass and rate of cover between rows of sugarcane were determined through six assessments in the first half of 2008. At the end of the evaluation (116 days after planting) the results showed that the clones (CT96-3095, CT95-3079, CT95-1425, CT96-3024, CT92-1882) were not significantly superior to the two considered varieties (SP81-3250 and SP91-1049).
Initial development of sugar cane varieties and clones in Oxisol, Aparecida do Taboado, Mato Grosso do Sul, Brazil
Keywords: Leaf area index; Saccharum spp.; Suppressive environment; Saccharum